최빈개도국 무관세·무쿼터 부여가 국내에 미치는 영향 분석 - 임송수 (한국농촌경제연구원, 2007)
This study aims to provide ways for Korea to expand the provision of preferential market access to the Least-Developed Countries (LDCs). Two criteria have been adopted to minimize potential adverse effects on domestic farm sectors. Primary criteria include identifying tariff lines with very low applied tariff rates and sorting out commodities subject to either low bounded or being eliminated as agreed upon bilateral trade agreements between Korea and other trading partners. To refine the results from applying primary criteria, the following supplementary criteria have been explored: imports with low market shares, commodities which are not or minimally produced in the country and commodities which are not exported by the LDCs to a large extent. Analytical results show Korea may designate up to 78 percent of its tariff lines as duty-free market access for the LDCs. Researchers: Lim, Song-Soo and Shin, You-Seon Research period: 2007. 7. - 2007. 11. E-mail address: songsoo@krei.re.kr